Pemanfaatan Gel Ekstrak Belimbing Wuluh sebagai Antibakteri Penyembuh Luka Diabetes Melitus Tipe II pada Tikus yang Terinduksi Stz-Na - Muna, Laili; Unsa Izzati; Rafiastiana Capritasari; Febriana Astusi (Universitas Tidar, 2025)
Diabetes is a degenerative disease with a reasonably high prevalence rate. This is due to the community's low lifestyle, so there is an uncontrolled increase in glucose levels in the blood. If this condition is not handled properly, increased blood glucose levels will cause complications in the form of wounds that are difficult to heal. Improper treatment can result in infection and damage, so the affected body part can be amputated. The treatment on the market is clindamycin, an antibiotic that can cause resistance if it is used in the long term. The use of the star fruit extract of Belimbing wuluh, which has a mechanism as antibacterial properties, is a treatment option to reduce the risk of using antibiotics. The purpose of this study was to determine the effectiveness of using star fruit water extract as a wound closure developed into a gel preparation. The group in this study was divided into 6 test groups, namely the non-diabetic group (1 group) and the STZ-Na-induced diabetes group (5 groups). The test treatment of Belimbing wuluh water extract was divided into three concentration range groups, which are 2.5%, 5%, and 10%, with a positive control ratio of clindamycin, and the observation of diabetes parameters was weight loss and percentage of wound closure. The results showed that the decrease in blood glucose levels (IBD) affected the wound closure rate, a macroscopically important parameter for accelerating the wound healing process (PL). Weight loss in test animals is also a parameter of type 1 DM due to STZ-Na induction. In the P3 group, the %PL result was 40%, which was better than the P1 of 9.33%. However, it was no better than the clindamycin-positive control group of 52.67%. In the wound healing process, the higher the concentration of Belimbing wuluh extract used, the faster the wound healing process. This is due to the content of secondary metabolites in Belimbing wuluh, which act as antibacterial agents.